Control-Based Resource Management for Storage of Video Streams. Issue 2 (2020) - Martins, Alexandre; Lindberg, Mikael; Maggio, Martina; Årzén, Karl-Erik
Abstract: Distributed surveillance systems typically consist of multiple cameras that need to store some fraction of their video streams at a central storage node. The disk space of this node constitutes a shared resource. In the paper the disk space allocation is formulated as a PI control problem and a new method for enforcing global resource constraints inspired by anti-windup tracking is proposed. The approach is evaluated by simulations.